Bacteroides fragilis RecA protein overexpression causes resistance to metronidazole - Steffens, Laura S. (Elsevier, 2010)
Bacteroides fragilis is a human gut commensal and an opportunistic pathogen causing anaerobic abscesses and bacteraemias which are treated with metronidazole (Mtz), a DNA damaging agent. This study examined the role of the DNA repair protein, RecA, in maintaining endogenous DNA stability and its contribution to resistance to Mtz and other DNA damaging agents. RT-PCR of B. fragilis genomic DNA showed that the recA gene was co-transcribed as an operon together with two upstream genes, putatively involved in repairing oxygen damage. A B. fragilis recA mutant was generated using targeted gene inactivation. Fluorescence microscopy using DAPI staining revealed increased numbers of mutant cells with reduced intact double-stranded DNA. Alkaline gel electrophoresis of the recA mutant DNA showed increased amounts of strand breaks under normal growth conditions, and the recA mutant also showed less spontaneous mutagenesis relative to the wild type strain. The recA mutant was sensitive to Mtz, ultraviolet light and hydrogen peroxide. A B. fragilis strain overexpressing the RecA protein exhibited increased resistance to Mtz compared to the wild type. This is the first study to show that overexpression of a DNA repair protein in B. fragilis increases Mtz resistance. This represents a novel drug resistance mechanism in this bacterium.